Early hydroxychloroquine retinopathy: optical coherence tomography abnormalities preceding Humphrey visual field defects. Issue 11 (28th February 2019) - Garrity, Sean T; Jung, Joo Yeon; Zambrowski, Olivia; Pichi, Francesco; Su, Daniel; Arya, Malvika; Waheed, Nadia K; Duker, Jay S; Chetrit, Yaïr; Miserocchi, Elisabetta; Giuffrè, Chiara; Kaden, Talia R; et al.
Abstract : Background/Aims: Hydroxychloroquine (HCQ) retinopathy may result in severe and irreversible vision loss, emphasising the importance of screening and early detection. The purpose of this study is to report the novel finding of early optical coherence tomography (OCT) abnormalities due to HCQ toxicity that may develop in the setting of normal Humphrey visual field (HVF) testing. Methods: Data from patients with chronic HCQ exposure was obtained from seven tertiary care retina centres. Ten patients with HCQ-associated OCT abnormalities and normal HVF testing were identified. Detailed analysis of the OCT findings and ancillary tests including colour fundus photography, fundus autofluorescence, multifocal electroretinography and microperimetry was performed in these patients. Results: Seventeen eyes from 10 patients illustrated abnormalities with OCT and normal HVF testing. These OCT alterations included (1) attenuation of the parafoveal ellipsoid zone and (2) loss of a clear continuous interdigitation zone. Several eyes progressed to advanced parafoveal outer retinal disruption and/or paracentral visual field defects. Conclusion: Patients with high risk HCQ exposure and normal HVF testing may develop subtle but characteristic OCT abnormalities. This novel finding indicates that, in some cases of early HCQ toxicity, structural alterations may precede functional impairment. It is therefore important to employ a screening approach that includes OCT to assess for these early findings. Ancillary testing should be considered in cases with suspicious OCT changes and normal HVFs.